Isoquinoline Alkaloids and antimalarial properties of Popowia Perakensis extract - Saripah Salbiah Syed Abd. Aziz (Tanjong Malim, 2009)
Isoquinoline Alkaloids and antimalarial properties of Popowia Perakensis extract by Saripah Salbiah Syed Abd. Aziz